ANALYSIS AND DESIGN OF INFORMATION SYSTEM SALES IN CV. ANUGRAH JAYA SURABAYA - Putri K. K., Brilliani Ayunda; Wulandari, Sri Hariani Eko; Santoso, Rudy (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
CV. Anugrah Jaya is sales distributor company that have priority of selling pipe and fitting. The company is established in 2013 at Imam Bonjol 31 Surabaya to run their company activities and has 8 employees. This company sells various pipes and fittings that the items total is about 300 items. The company still doing manual recording which use Microsft Excel where frequently mistake in data input proccess so as to produce information less than accurate. This causing problems on selling transaction recording, items requisition, items price searching, and stock calculation. Based on problems above, company need a sales information system. Because the company does not have a blueprint of sales information systems and did not know in detail what is required in the sales informationsystem in CV. Anugrah Jaya Surabaya, so in this research Analysis and Designingsales information systems in CV. Anugrah Jaya Surabaya expected to be developed and helping admin in resolving every his job.